An integrated molecular modeling approach for the tryptase monomer–curcuminoid recognition analysis: conformational and bioenergetic features - Pathomwat Wongrattanakamon (2018)
© 2018, Springer Science+Business Media, LLC, part of Springer Nature. Human mast cell tryptase has been shown as an activating enzyme in matrix degradation process. The previous study suggest that tryptase either alone or in joining with activation of metalloproteinases, can associate in extra cellular matrix damage and the possible destruction of the basement membrane resulting in photoaging. Therefore the inhibition of tryptase activity is one of the most important therapeutic strategies against the photoaging. Curcumin has been shown to be a potential agent for preventing and/or treating the photoaging induced by UV radiation. However, the protective effect of curcumin against the photoaging through the tryptase inhibition is still inadequately understood. In this work, computational methods to characterize the structural framework and define the atomistic details of the determinants for the tryptase inhibition mechanism by curcuminoids were performed. By molecular docking, three putative binding models able to efficiently bind all curcuminoids were identified. Analysis of molecular dynamics simulations revealed that cyclocurcumin, curcumin glucuronide, and curcumin, the most effective inhibitors from the three models, modified significant tryptase monomer rigidity by binding in all the possible sites. The result of these binding events is the suppression of the functional enzymatic motions involving the binding of substrates to the catalytic site. On the basis of this finding may thus be beneficial for the development of new natural inhibitors for the therapeutic remedy of photoaging, targeting and modulating the activity of tryptase.